2014
DOI: 10.1007/s10162-013-0437-5
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Electro-Neural Interface of Cochlear Implant Users Using Psychophysics, CT Scans, and Speech Understanding

Abstract: This study examines the relationship between focused-stimulation thresholds, electrode positions, and speech understanding in deaf subjects treated with a cochlear implant (CI). Focused stimulation is more selective than monopolar stimulation, which excites broad regions of the cochlea, so may be more sensitive as a probe of neural survival patterns. Focused thresholds are on average higher and more variable across electrodes than monopolar thresholds. We presume that relatively high focused thresholds are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
173
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(201 citation statements)
references
References 34 publications
23
173
3
2
Order By: Relevance
“…In damaged ears, thresholds for activation can be elevated due to loss of the most sensitive fibers or increased distance between the implant electrodes and the most sensitive nerve fibers (Bierer and Faulkner, 2010;Long et al, 2014). Our data showed that in some ears, stimulation sites that had shallow slopes did also tend to have higher absolute detection thresholds.…”
Section: B Effects Of Neural Survival On Speech Recognition In Noisesupporting
confidence: 47%
“…In damaged ears, thresholds for activation can be elevated due to loss of the most sensitive fibers or increased distance between the implant electrodes and the most sensitive nerve fibers (Bierer and Faulkner, 2010;Long et al, 2014). Our data showed that in some ears, stimulation sites that had shallow slopes did also tend to have higher absolute detection thresholds.…”
Section: B Effects Of Neural Survival On Speech Recognition In Noisesupporting
confidence: 47%
“…Spatial summation of stimulation would not only cause spectral information to smear but also cause the subgroup of auditory fibers to be stimulated at a rate that is much higher than the singleelectrode rate, increasing the probability of neural adaptation (Boulet et al, 2016). Because neural survival, electrode position, and other pathological variables are not homogeneous across the tonotopic axis in an implanted ear (Nadol, 1997;Long et al, 2014), some stimulation sites are expected to interact more than others. The hypothesis tested in the current study was whether removing the stimulation sites estimated to produce broad neural excitation would improve spectral resolution, which in turn would improve speech recognition.…”
Section: Discussionmentioning
confidence: 99%
“…The factors that contribute to channel interaction include but are not limited to electrode impedance, electrode position relative to the modiolus, and survival pattern of the auditory nerve fibers (e.g., Long et al, 2014). High impedance, large electrode-neuron distance, or a significant loss of nerve fibers near the stimulation site, would result in an increased spread of neural excitation from the targeted tonotopic place.…”
Section: Introductionmentioning
confidence: 99%
“…By optimizing the JND parameters for model fits to each subject's data in the quiet condition, we are controlling for individual factors that affect CI users' discrimination for place of stimulation in the cochlea such as electrode placement, cochlear size, neural survival, etc. (Bierer, 2010;Long et al, 2014). From a modeling perspective it is more parsimonious to minimize the number of degrees of freedom, and assuming an underlying constant JND for place of stimulation allows us to do so.…”
Section: Modeling Assumptionsmentioning
confidence: 99%